Transformative church : new ecclesial models and the theology of Jurgen Moltmann. - Oden, Patrick David (Emerging scholars., 2015)
Throughout the course of his theological career, Jürgen Moltmann has been interested in the ecclesial and societal consequences of systematic theology and what each doctrine means for our life in this world. The Transformative Church explores these concerns in Moltmann's major texts and highlighting themes relevant for a transformative ecclesiology. Patrick Oden constructs a substantive transformative ecclesiology embedded in this world: we are to become in the church who we are to be in this world, whole in Christ so as to be a messianic people in any context.